VITAMIN D DEFICIENCY RICKETS – A CASE SERIES: A TIP OF THE ICEBERG - N, Naveen; WSL, Jeanne; YK, Cheah (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Vitamin D deficiency is the most common cause of rickets worldwide. In Malaysia, owing to the abundant sunlight exposure, it is believed to be uncommon, however it is likely to be under-reported. In addition, dietary calcium deficiency is an important cause of nutritional rickets in children above 1 year old in developing countries. RESULTS We report a case-series of 4 unrelated Malaysian children (aged between 1 to 3) born in Istanbul, Turkey presented with the classical clinical features and biochemical changes of rickets. They were all exclusively breast-fed during infancy with poor dietary calcium intake. Their workup showed normal Calcium, high Alkaline Phosphatase, low Vitamin D and high Parathyroid hormone levels, with radiographic changes of fraying and spraying of the wrist, consistent with Vitamin D Deficiency Rickets. Bowing of legs and widening of wrists joints also seen. Low maternal Vitamin D levels also support the diagnosis. All four children were treated with cholecalciferol (vitamin D3) and short-term calcium supplements. The children showed improvements in growth and normalization of biochemical parameters on follow-ups. CONCLUSION Meta-analysis in Turkish populations have shown high prevalence of Vitamin D deficiency leading to their national policy of vitamin D supplementation for infants. Our patients in this case series were neither immunized nor received the appropriate supplements during their stay in Istanbul, Turkey. Maternal vitamin D deficiency, restricted sunlight exposure due to clothing style and seasonal variations, poor dietary calcium intake were all the contributing factors to the nutritional rickets in our patients. Maternal Vitamin D levels could serve as an early indicator of possible deficiency if detected early. Awareness amongst our population was scarce, leading to a delay in seeking treatment/intervention. This case series aims to highlight the importance of vitamin D supplementation as well as ensuring adequate dietary calcium in prevention of nutritional rickets